New perspectives on screening and early detection of endometrial cancer. Issue 12 (28th June 2019) - Costas, Laura; Frias‐Gomez, Jon; Guardiola, Magdalena; Benavente, Yolanda; Pineda, Marta; Pavón, Miquel Á.; Martínez, José M.; Climent, Maite; Barahona, Marc; Canet, Júlia; Paytubi, Sonia; Salinas, Mónica; et al.
Abstract : Due to the anatomical continuity of the uterine cavity with the cervix, genomic exploitation of material from routine Pap smears and other noninvasive sampling methods represent a unique opportunity to detect signs of disease using biological material shed from the upper genital tract. Recent research findings offer a promising perspective in the detection of endometrial cancer, but certain questions need to be addressed in order to accelerate the implementation of novel technologies in a routine screening or clinical setting. We discuss here new perspectives on detection of endometrial cancer using genomic and other biomarkers in minimally invasive sampling methods with a special focus on public health classic screening criteria, highlighting current gaps in knowledge.